Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada PT Ultrajaya Milk Industry Tahun 2020-2022 - Hilda Melia Faradila; Andrik Gastri Widjatmiko (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
In the current era of very tight business competition, companies are required to improve their financial performance. To be able to assess the company's financial performance, all interested parties need to know the company's financial condition as seen from the company's financial reports. To assess the company's financial performance, it can be shown through the financial reports presented by the company management. The importance of the liquidity ratio for financial performance is because liquidity has a fairly close relationship with the company's ability to earn profits (profitability), namely liquidity shows the level of availability of working capital needed for operational activities. Having sufficient working capital makes it possible for the company to operate optimally and not experience difficulties due to the financial crisis. However, excessive working capital actually shows that there are unproductive funds and gives the impression that the company is releasing them to make a profit. Ideally, the company's working capital should be available in sufficient quantities to finance the company's various activities, which means there is no shortage of capital and no idle resources. In this way, the company's ability to improve its financial performance on its assets is maximized, and the current ratio is one of the components of the liquidity ratio used in this research.